1999
DOI: 10.1017/s0007114599001063
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrients: highlights and research challenges from the 1994–5 National Diet and Nutrition Survey of people aged 65 years and over

Abstract: The aims of the National Diet and Nutrition Survey series are summarized, and the new National Diet and Nutrition Survey of people aged 65 years and over is explored, with particular emphasis on micronutrient intakes and status indices. Mean nutrient intakes were generally satisfactory for most micronutrients, but intakes of vitamin D, Mg, K and Cu were low. Intakes of vitamin D were far below the reference nutrient intake for people aged 65 years and over, and there was also biochemical evidence of vitamin D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
99
1
2

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(112 citation statements)
references
References 11 publications
6
99
1
2
Order By: Relevance
“…In addition, it is likely that vitamin B 12 status is dependent on longterm, as distinct from short-term variations in vitamin B 12 intakes. This is also suggested by the observation that the correlation between serum vitamin B 12 and vitamin B 12 intake is relatively weak (Finch et al, 1998;Bates et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, it is likely that vitamin B 12 status is dependent on longterm, as distinct from short-term variations in vitamin B 12 intakes. This is also suggested by the observation that the correlation between serum vitamin B 12 and vitamin B 12 intake is relatively weak (Finch et al, 1998;Bates et al, 1999).…”
Section: Discussionmentioning
confidence: 86%
“…As part of a series of government-commissioned surveys of several age-groups of the British population in the final decade of the twentieth century, a survey of people aged 65 y and over was carried out in 1994 -1995 (Finch et al, 1998;Bates et al, 1999). Estimates of mean daily nutrient intakes (from a 4 day weighed diet record), a sociodemographic questionnaire and a fasting blood sample for biochemical and other status measurements were included.…”
Section: Methodsmentioning
confidence: 99%
“…It is therefore of some concern that in the latest UK National Diet and Nutrition Survey of people aged 65 and over, the intake of copper fell below the RNI in 82% of free-living participants and in 90% of those in institutions, while the corresponding figures for zinc were 62% and 54% [97]. Though intake figures were better in the survey of younger adults, even then, median copper intake was below the RNI in women (82% of RNI) [98].…”
Section: Zinc and Copper Statusmentioning
confidence: 99%
“…For example, Fukao et al (1996) have shown that serum b-carotene concentrations were modi®ed by both alcohol consumption and smoking independently after adjusting for age, intake of b-carotene, BMI and cholesterol levels. In addition, Bates et al (1999) have shown that plasma b-carotene, b-cryptoxanthin, lutein, lycopene and a-tocopherol were strongly negatively correlated with increasing socio-economic status and with north-south gradients in Great Britain. Similarly, in the Caerphilly cohort, all of the measured carotenoids (except lycopene with socio-economic status) were negatively correlated with socio-economic status, smoking and alcohol intake (Mulholland et al, 1999).…”
Section: Discussionmentioning
confidence: 99%